2015
DOI: 10.1186/s40608-015-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of therapeutic plasma exchange on plasma levels and total removal of adipokines and inflammatory markers

Abstract: BackgroundAside from well-established inflammatory mediators adipokines have recently been found to play an important role in a variety of immunologic diseases. Therapeutic plasma exchange (TPE) is an established treatment modality for the acute removal of pathophysiological relevant disease mediators. The aim of this study was to determine adipokine removal during TPE therapy.Methods21 Caucasian patients (10 females, 11 males) with an indication for TPE using albumin as exchange fluid received two consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…If FFP is not the chosen replacement fluid, on top of the removal of disease mediators, plasma exchange could potentially also deplete the patient of important plasma constituents including clotting factors, transport proteins, inflammatory and cardiac biomarkers, adipose tissue–derived hormones, and so forth . Depending on the specific plasma constituent, the removal of it might have a specific impact for the treatment of the underlying disease .…”
Section: Discussionmentioning
confidence: 99%
“…If FFP is not the chosen replacement fluid, on top of the removal of disease mediators, plasma exchange could potentially also deplete the patient of important plasma constituents including clotting factors, transport proteins, inflammatory and cardiac biomarkers, adipose tissue–derived hormones, and so forth . Depending on the specific plasma constituent, the removal of it might have a specific impact for the treatment of the underlying disease .…”
Section: Discussionmentioning
confidence: 99%
“…This study included 21 patients with the need for TPE as reported elsewhere [ 12 ]. The inclusion criteria were:…”
Section: Methodsmentioning
confidence: 99%
“…[ 5 ] Moreover, despite the lack of solid data, TPE is used in the intensive care setting for e.g. sepsis with multi organ failure or hypertriglyceridemia induced pancreatitis [ 6 , 7 ] as it removes a plethora of pro-inflammatory cytokines [ 8 ].…”
Section: Introductionmentioning
confidence: 99%